2013
DOI: 10.1179/1743132813y.0000000167
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation to augment recovery from severe traumatic brain injury impeding consciousness: a prospective pilot clinical trial

Abstract: Objectives-Traumatic brain injury has a high morbidity and mortality in both civilian and military populations. Blast and other mechanisms of traumatic brain injury damage the brain by causing neurons to disconnect and atrophy. Such traumatic axonal injury can lead to persistently vegetative and minimally conscious states, for which limited treatment options exist, including physical, occupational, speech and cognitive therapies.More than 60,000 patients have received vagus nerve stimulation for epilepsy and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 164 publications
1
27
0
Order By: Relevance
“…More recent studies have implicated vagus nerve activity, especially the efferent splenic component, in reducing systemic inflammation (Borovikova et al, 2000;Rosas-Ballina et al, 2008;Olofsson et al, 2012). Consistent with this, we have previously demonstrated that splenectomy markedly decreased TBI-triggered BBB permeability, suggesting a role for spleen-mediated systemic inflammation in BBB breakdown (Walker et al, 2010).…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…More recent studies have implicated vagus nerve activity, especially the efferent splenic component, in reducing systemic inflammation (Borovikova et al, 2000;Rosas-Ballina et al, 2008;Olofsson et al, 2012). Consistent with this, we have previously demonstrated that splenectomy markedly decreased TBI-triggered BBB permeability, suggesting a role for spleen-mediated systemic inflammation in BBB breakdown (Walker et al, 2010).…”
Section: Introductionsupporting
confidence: 86%
“…Breakdown of the BBB is an important secondary TBI pathology as it can cause further brain damage by allowing the infiltration of inflammatory cells and the uncontrolled access of circulating fluid, proteins, and signaling molecules to affected brain tissues (Tanno et al, 1992;Stahel et al, 2000;Zhao et al, 2007). These events exacerbate ongoing brain inflammation and can contribute to cerebral edema and increased intracranial pressure, leading to decreased cerebral blood flow, secondary tissue damage, brain herniation, and poor outcome (Raghupathi, 2004;Kochanek et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the above mentioned, more and more results of taVNS on neurological and mental disorders was achieved including tinnitus [24,25], chronic migraine [26], schizophrenia [27,28], postoperative cognitive dysfunction [29]. clearance will be the first step in determining the efficacy of VNS for improvement of consciousness after severe brain injury [30]. Inspired by this, our team is focusing on transcutaneous auricular vagus nerve stimulation (taVNS) on patients with disorder of consciousness (DOC).…”
Section: Transcutaneous Auricular Vagus Nerve Stimulation (Tavns) On mentioning
confidence: 99%